Pengaruh Influencer Endorsement dan Electronic Word Of Mouth (eWOM) Terhadap Minat Beli Kuliner Halal pada Gen Z Pengguna Tiktok - Aquila, Marisa Saba; Rohmaningtyas, Nurwinsyah (Jurnal Ekonomika dan Bisnis Islam, 2026)
This study aims to analyze the influence of Influencer Endorsement and Electronic Word of Mouth (eWOM) on purchase intention of halal culinary products among Generation Z TikTok users in Surabaya. Influencer Endorsement is measured through three dimensions: Attractiveness, Trustworhtiness, and Expertise. This research employs a quantitative associative approach using primary data collected through questionnaires distributed to Generation Z respondents who reside in Surabaya and actively use TikTok. A total of 130 respondents participated in this study. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The results indicate that Attractiveness, Trustworhtiness, and Expertise of Influencer Endorsement have a significant positive effect on purchase intention toward halal culinary products among Generation Z TikTok users. Influencers who possess strong visual appeal, credibility, and relevant knowledge are able to create positive perceptions and encourage consumers’ intention to purchase promoted halal culinary products. Conversely, eWOM does not have a significant effect on purchase intention. This finding suggests that information and online reviews circulating on TikTok are perceived as supplementary considerations amid the rapid flow of digital content, leading Generation Z to be more selective in processing online information before forming purchase intentions.